Prevalence of premature loss of deciduous teeth and its relationship with gender among children from Acapulco, Guerrero: a cross-sectional study - Juan J. Hernández-Palacios; Jovanna J. Castañeda-Ayala; Carlos A. Juárez-Medel; Juan E. Barrios-Flores; Janitzie Hernández-Clemente; Evangelina Gutiérrez-Ventura (Boletín Médico del Hospital Infantil de México, 2022)
Background: Premature loss of deciduous teeth is the exfoliation or extraction before physiological replacement with < 50% or < 75% of the root of the substitute tooth formed or if there is > 1 mm of alveolar bone covering the permanent successor tooth organ. This study aimed to estimate the prevalence of premature tooth loss in children and identify associated factors in a health center in Acapulco, Guerrero. Methods: We conducted a cross-sectional study in which we collected information from 109 clinical records of children examined from January 2019 to August 2021. Sociodemographic data of the children and parents were collected: socioeconomic level, non-pathological personal history, and the history of premature deciduous tooth loss. Multivariate analysis to identify factors associated with premature deciduous tooth loss was performed with CIETmap statistical software. Odds ratio (OR) and 95% confidence interval (CI) were calculated to estimate the strength of the association. Results: The prevalence of premature loss of primary teeth was 40% (43/109). The leading cause was caries (84%, 36/43). The tooth organ with the highest loss occurrence was the lower right second molar (33%, 14/43). Gender was identified as an associated factor, with males having a higher risk of loss (ORa = 2.97; CI95% = 1.33-6.65). Conclusions: Our results were similar to those reported in other studies. Strategies aimed at health promotion directed at parents and children should be reinforced.